The impact of universal home visits with pregnant women and their spouses on maternal outcomes: a cluster randomised controlled trial in Bauchi State, Nigeria - Cockcroft, Anne (BMJ Glob Health, 2019)
INTRODUCTION: Maternal mortality in Nigeria is extremely high. Access to quality antenatal and obstetric care is limited. In Bauchi State, we found maternal morbidity was associated with domestic violence, heavy work in pregnancy, ignorance of danger signs, and lack of spousal communication. This cluster randomized controlled trial tested the impact of universal home visits that discussed these upstream risk factors with pregnant women and their spouses, to precipitate household actions protecting pregnant women. METHODS: We randomly allocated four wards in Toro Local Government Authority to immediate or delayed intervention. Female and male home visitors visited all pregnant women and their spouses in the two intervention wards every 2 months. We compared completed pregnancies between intervention and pre-intervention wards after 1 year. Primary outcomes were pregnancy, delivery, and postnatal complications, analysed with intention to treat using a cluster t-test. Ancillary analysis examined the influence of baseline and health service use differences. RESULTS: Among 1837 women in intervention wards and 1853 women in pre-intervention wards, the intervention reduced problems in pregnancy and post partum: raised blood pressure (relative risk reduction (RRR) 0.120, cluster-adjusted 95% CI (CIca) 0.045 to 0.194; risk difference (RD) 0.116, 95% CIca 0.042 to 0.190) and swelling of face or hands (RRR 0.271, 95% CIca 0.201 to 0.340; RD 0.264, 95% CIca 0.194 to 0.333) and postpartum sepsis (RRR 0.399, 95% CIca 0.220 to 0.577; RD 0.324, 95% CIca 0.155 to 0.493). The intervention reduced the targeted upstream risk factors such as heavy work during pregnancy (RRR 0.234, 95% CIca 0.085 to 0.383; RD 0.222, 95% CIca 0.073 to 0.370). It did not increase use of antenatal care, institutional delivery or skilled birth attendance. CONCLUSION: Home visits reduced upstream maternal risks, improving maternal outcomes without increased use of health services. This could have implications in other settings with poor access to quality antenatal and delivery care services. TRIAL REGISTRATION: ISRCTN82954580.